Threonine-lysine ratio on the requirements of digestible lysine in diets for broilers - Iván Camilo Ospina-Rojas; Alice Eiko Murakami; Cinthia Eying; Karla Paola Picoli; Claudio Scapinello; Cristiane Regina do Amaral Duarte (Acta Scientiarum: Animal Sciences, 2014)
Two experiments were performed to determine the influence of threonine-lysine (Thr:Lys) ratio on requirements of digestible lysine (Lys) in low crude protein diets for broilers in the growth phase. In the first experiment, a total of 480 Cobb 500 male broilers were distributed in a completely randomized experimental design with four dietary Thr:Lysratio (57.0; 60.5; 64.0 and 67.5%) and with five replicates of 24 birds each. No significant differences were reported in weight gain, feed intake, poultry manure humidity, carcass and meat yields. However, the feed conversion was increased linearly as dietary Thr:Lysratio was increased. In the second experiment, a total of 400 Cobb 500 male broilers were distributed in a completely randomized experimental design with four digestibleLyslevels (1.005, 1.045, 1.085 and 1.125%), and with four replicates of 25 birds each. No significant differences were reported in performance, poultry litter humidity and carcass and meat yields. Lys levels of 1.005% and Thr:Lysat 57% were sufficient to maximize the performance and carcass yield of broilers during the growth phase when fed on low crude protein diets.